2021
DOI: 10.3389/fpsyg.2021.643974
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental and Hedonic Motives for Emotion Regulation in Musical Practice

Abstract: Emotion regulation literature often emphasizes that individuals regulate their emotions for hedonic reasons. However, there is increasing support for an instrumental approach to emotion regulation. This approach suggests that emotions are regulated if they are believed to be beneficial to the pursuit of personally relevant goals. When pursuing a long-term goal, an individual may forego immediate, hedonic emotional reward in order to maximize the instrumental benefits of emotions. The current study investigates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
(123 reference statements)
0
2
0
1
Order By: Relevance
“…Another study revealed a positive and significant relationship between the festival program and hedonism (Grappi & Montanari, 2011). Literature on emotion regulation emphasizes that individuals' emotions are often shaped by hedonic reasons (Madden & Jabusch, 2021). Music festivals are indicated to encompass hedonic satisfaction in this regard (Saragih & Amelia, 2020).…”
Section: Extended Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Another study revealed a positive and significant relationship between the festival program and hedonism (Grappi & Montanari, 2011). Literature on emotion regulation emphasizes that individuals' emotions are often shaped by hedonic reasons (Madden & Jabusch, 2021). Music festivals are indicated to encompass hedonic satisfaction in this regard (Saragih & Amelia, 2020).…”
Section: Extended Summarymentioning
confidence: 99%
“…Duyguların düzenlenmesine ilişkin alanyazın bireylerin duygularının sıklıkla hedonik nedenlere bağlı olarak şekillendiğini vurgulamaktadır (Madden & Jabusch, 2021). Eğlenceli ve zevkli olarak tanımlanan her tüketici deneyiminin içinde tüketicilerin elde ettiği en önemli fayda hedonik değerdir (Grappi & Montanari, 2011).…”
Section: İlgili Literatür Ve Hipotez Gelişimiunclassified
“…This study used data collected but only partly analyzed from an earlier study on emotion regulation behaviour in musical practice (Breaden Madden and Jabusch, 2021). A total of 421 musicians completed an online questionnaire distributed via their host music institution (conservatoire, orchestra, university of music, etc.).…”
Section: Participantsmentioning
confidence: 99%